Effect of sputtering input power on structural inhomogeneities in as-sputtered Fe-Hf-N thin films - Kim, KH; Kim, YH; Kim, J; Han, SH; Kim, HJ (ELSEVIER SCIENCE BV, 2000)
The magnetic properties of Fe-Hf-N thin films, deposited by a reactive RF magnetron sputtering method, depend on input powers (150, 300, 450, 550 W). The gamma'-Fe4N phase is observed in all samples by TEM and ESCA, FMR results also show extra resonance peaks with weak intensity, observed at a higher field than that of main mode-(alpha-Fe) except 450 W. The calculated frequency dependency of permeability does not coincide with experimental values except 450 W. These discrepancies are expected to be due to the local anisotropy created by an inhomogeneous magnetic phase. (C) 2000 Published by Elsevier Science B.V. All rights reserved.
Keywords: FERROMAGNETIC-RESONANCE; MAGNETIC-PROPERTIES